Household air pollution: national and subnational estimates in Bangladesh, India, Indonesia, Nepal, and the Philippines - Wang, Wenjuan; Assaf, Shireen; Mayala, Ben; Davis, Lwendo Moonzwe (DHS Working Papers No. 164, 2020)
Household air pollution (HAP) is a major public health concern in many low- and middle-income countries. In the past few decades, population growth has led to increases in the number of individuals cooking with solid fuels and exposure to biomass and coal smoke. Globally, millions of deaths each year are linked to indoor air pollution, with women and children affected disproportionately. There is limited understanding of trends and geographic variation in HAP, which has made targeting of interventions challenging. This paper identifies HAP trends; examines associations between HAP and household characteristics in Bangladesh, India, Indonesia, Nepal, and the Philippines; and estimates district-level exposure to HAP in all of these countries except for Indonesia, where global positioning system data were lacking. The results indicated a decreasing overall trend in use of solid fuel for cooking in these countries. However, disparities persisted in all countries. The greatest reductions in use of solid fuel were among wealthier households, while the poorest households continued to be the most affected by HAP. The district-level estimates of HAP are summarized in maps that clearly highlight hot spots that can be targeted for interventions.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#720-OAA-18C-00083). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.